Sources of endogenous glucose production in the Goto-Kakizaki diabetic rat - Sena, C. M. (2007)
Plasma glucose, insulin and glucose tolerance were quantified in diabetic Goto–Kakizaki (GK) rats (342 ± 45 g, n = 5) and compared with weight-matched non-diabetic Wistars (307 ± 30 g, n = 8). Compared to Wistars, GK rats had higher fasting plasma insulin (219 ± 50 versus 44 ± 14 pmol/l, P < 0.002) and glucose (9.2 ± 2.3 versus 5.5 ± 0.5 mmol/l, P < 0.025). GK rats showed impaired glucose tolerance (IPGTT 2 h plasma glucose = 14 ± 1.5 versus 6.4 ± 0.1 mmol/l, P < 0.001). Endogenous glucose production (EGP) from glycogenolysis, phosphoenolpyruvate (PEP) and glycerol after 6 hours of fasting was quantified by a primed infusion of [U–13C]glucose and 2H2O tracers and 2H/13C NMR analysis of plasma glucose. EGP was higher in GK compared to Wistar rats (191 ± 16 versus 104 ± 27 μmol/kg per min, P < 0.005). This was sustained by increased gluconeogenesis from PEP (85 ± 12 versus 35 ± 4 μmol/kg per min, P < 0.02). Gluconeogenesis from glycerol was not different (20 ± 3 in Wistar versus 30 ± 6 μmol/kg per min for GK), and glycogenolysis fluxes were also not significantly different (76 ± 23 μmol/kg per min for GK versus 52 ± 19 μmol/kg per min for Wistar). The Cori cycle accounted for most of PEP gluconeogenesis in both Wistar and GK rats (85 ± 15% and 77 ± 10%, respectively). Therefore, increased gluconeogenesis in GK rats is largely sustained by increased Cori cycling while the maintenance of glycogenolysis indicates a failure in hepatic autoregulation of EGP